Stunting and its association with feeding problem among 6 to 59 months children in Kuantan district - Kamaruzaman, Nor Azam; Musa, Noraini; Pasi, Hafizah (Academy of Family Physicians of Malaysia (AFPM) and Family Medicine Specialist Association of Malaysia, 2023)
This study was a case-control study involving 160 respondents with the objective to determine the association between stunting and feeding problems among infants and young children attending health clinics in the Kuantan district. Children with any feeding problem have more than four-time significantly higher risk of becoming stunted (OR: 4.2 [95% CI 1.4-12.8]) as compared to children with no feeding problem. Children with inadequacy in feeding components; frequency, variety and amount of meal each have significantly three-time higher risk (OR: 2.8 [95% CI 1.1-6.9]), four-time higher risk (OR: 4.2 [95% CI 1.4-12.3]) and six-time higher risk (OR: 6.2 [95% CI 2.7-14.5]) of becoming stunted as compared to children with adequate feeding.